Flow Dynamics in Brain Aneurysms: A Review of Computational and Experimental Studies - Prantik Roy Chowdhury; Victor K. Lai; Ruihang Zhang (Biomechanics)
A brain aneurysm is a structural deterioration of the arterial wall in the brain, resulting in the formation of a bulge in or ballooning of a blood vessel. Around 3–5% of the global population is affected by brain aneurysms, wherein only a small fraction results in rupture. Although an unruptured aneurysm is typically asymptomatic and not immediately life threatening, it poses a potential risk of rupture, which can lead to severe health complications or mortality. Therefore, it is crucial to detect and treat aneurysms during the unruptured phase. Moreover, a comprehensive understanding of the flow dynamics within the aneurysm and its parent artery is essential for accurate diagnosis and the prevention of aneurysm recurrence. While prior reviews have focused on computational fluid dynamics (CFD) studies on brain aneurysms, particularly patient-specific models from studies conducted over a decade ago, a more recent review is necessary. Additionally, reviewing various studies on the fluid dynamic behavior of treated aneurysms is crucial. Thus, the advancements in both experimental and computational studies on brain aneurysms must be explored to better understand their underlying fluid flow mechanisms and to develop robust treatment strategies. This review aims to summarize the different types of brain aneurysms, the screening and treatment processes, the key hemodynamic factors, and the fluid dynamic characteristics observed in aneurysms before and after treatment.